The importance of antibody dependent cell-mediated cytotoxicity (ADCC) for breast cancer response to trastuzumab - Herceptin - Juranić Zorica D.; Stanojević-Bakić Nevenka; Nešković-Konstantinović Zora; Žižak Željko; Stanojković Tatjana; Radulović Siniša S.; Milošević Dušanka (Archive of Oncology, 2002)
In this work we investigated the direct or indirect (through ADCC) cytotoxic action of Herceptin, to two breast carcinoma cell lines: to MDA-MB 361, for HER-2, IHC score (3+) and to MDA-MB 453, IHC score (<2+). Cytotoxic action of Herceptin, of PBMC and of their combination (ADCC) was determined 48h later, indirectly, through the determination of target cell survival by MTT test. Preliminary results indicate that direct cytotoxicity of Herceptin against investigated breast carcinoma cells was very low, probably due to their high duplication time. However, the cytotoxic action of PBMC mediated through Herceptin as ADCC, was noted in investigation of cytotoxicity of some persons' PBMC.